Detection and significance of neuronal autoantibodies in patients with meningoencephalitis in Vientiane, Lao PDR. (6th April 2022) - Uy, Christopher E; Mayxay, Mayfong; Harrison, Ruby; Al-Diwani, Adam; Jacobson, Leslie; Rattanavong, Sayaphet; Dubot-Pérès, Audrey; Vongsouvath, Manivanh; Davong, Viengmon; Chansamouth, Vilada; Phommasone, Koukeo; Waters, Patrick; et al.
Abstract: Background: The importance of autoimmune encephalitis and its overlap with infectious encephalitides are not well investigated in South-East Asia. Methods: We report autoantibody testing, using antigen-specific live cell-based assays, in a series of 134 patients (cerebrospinal fluid and sera) and 55 blood donor controls (sera), undergoing lumbar puncture for suspected meningoencephalitis admitted in Vientiane, Lao People's Democratic Republic (PDR). Results: Eight of 134 (6%) patients showed detectable serum neuronal autoantibodies, against the N-methyl-D-aspartate and gamma-aminobutyric acid A receptors (NMDAR and GABAA R), and contactin-associated protein-like 2 (CASPR2). Three of eight patients had accompanying autoantibodies in cerebrospinal fluid (two with NMDAR and one with GABAA R antibodies), and in two of these the clinical syndromes were typical of autoimmune encephalitis. Three of the other five patients had proven central nervous system infections, highlighting a complex overlap between diverse infectious and autoimmune causes of encephalitis. No patients in this cohort were treated with immunotherapy, and the outcomes were poor, with improvement observed in a single patient. Conclusions: In Lao PDR, autoimmune encephalitis is underdiagnosed and has a poor prognosis. Empiric immunotherapy should be considered after treatable infectious aetiologies are considered unlikely. Awareness and diagnostic testing resources for autoimmune encephalitis should be enhanced in South-East Asia.